Does a delay in surgery for distal radial fractures affect patient outcome?. (January 2021) - Howard, Matthew; Curtis, Alex; Everett, Sam; Harries, Luke; Donaldson, Oliver; Sheridan, Barnaby
Current guidelines from the British Orthopaedic Association state that if fractures of the distal radius are operated on then this should take place within 3 days of injury for intra-articular fractures, 7 days for extra-articular fractures and 3 days when a trial of conservative management has failed. This retrospective cohort study aimed to assess whether there was any difference in outcome between patients receiving timely or delayed surgery, using the Patient-Rated Wrist Evaluation score at >12 months after injury as the primary outcome measure. Data from 380 patients treated at two district general hospitals over a 5-year period were obtained using electronic databases to capture the demographics and treatment details and postal questionnaires to assess current function. The study showed no statistical or clinical differences in outcome measures between the timely or delayed cohorts in any of the three treatment groups. Level of evidence: III